The effects of assisted and resisted plyometric training programs on vertical jump performance in adults: A systematic review and meta-analysis - Makaruk, H.; Starzak, M.; Suchecki, B.; Czaplicki, M.; Stojiljkovic, N. (Journal of Sports Science & Medicine, 2020)
Traditional, assisted and resisted plyometrics are considered to be effective training methods for improving vertical jump performance. The purpose of this systematic review and meta-analysis was to compare effectiveness of traditional, assisted and resisted plyometric methods on vertical jumping ability in adults. Available literature was searched using MEDLINE (via EBSCO), SPORTDiscus (via EBSCO), Scopus and Web of Science databases. The methodological quality of studies was assessed using the PEDro scale. Peer-reviewed studies were accepted only if they met all eligibility criteria: (a) healthy adults mean age > 18 years (b) training program based on plyometric exercises (c) the study reported on vertical jump height for the countermovement jump or drop jump performance. Of the 5092 articles identified, 17 studies were included in the qualitative and quantitative analyses. Both funnel plot analysis and Egger's test (p = 0.04) indicated publication bias for the comparison of resisted plyometrics and control condition. No publication bias was found for the other meta-analyses (p > 0.05). The effects of the traditional and assisted plyometric methods, when compared with the control condition (a non-plyometric condition), on jump height were moderate (SMD = 0.68, 95% CI 0.37 to 0.99, p < 0.0001; SMD = 0.70, 95% CI 0.20 to 1.20, p = 0.006, respectively). The effects of the resisted plyometric methods, when compared with the control condition, on a jump height was small (SMD = 0.48, 95% CI 0.17 to 0.79, p = 0.002). There were no significant differences between the training effects of the assisted and traditional plyometric interventions on jump height (SMD = 0.62, 95% CI -1.66 to 2.91, p = 0.59), nor between the resisted and traditional plyometric training programs (SMD = 0.2, 95% CI -0.19 to 0.23, p = 0.86). Traditional, assisted and resisted plyometric methods are effective training modalities for augmenting vertical jump performance in healthy adults. Resisted and assisted plyometric methods are equally effective as the traditional plyometric method in improving vertical jumping ability in healthy adults.